STRATEGI TALENT MANAGEMENT DALAM MENINGKATKAN RETENSI KARYAWAN BERPOTENSI TINGGI - Dewi, Susantriana; Yusuf, Ramdan; Tawil, Muhamad Risal; Tammubua, Milcha Handayani; Agustina, Wiwit (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze talent management strategies for increasing the retention of high-potential employees. The approach used was qualitative, with descriptive research. Data were collected through in-depth interviews, observations, and documentation with informants consisting of organizational leaders, human resource managers, and high-potential employees selected using purposive sampling techniques. Data analysis was conducted using an interactive model encompassing data reduction, data presentation, and conclusion drawing. Its validity was tested through triangulation of sources and methods. The results indicate that talent management strategies, including talent identification, competency development, and career and success planning, have a significant influence on increasing the retention of high-potential employees. Supporting factors such as effective leadership, competitive reinforcement, and a positive organizational culture contribute to retention success. However, implementation challenges remain, such as the lack of an integrated system and suboptimal program development. Therefore, organizations need to develop a comprehensive, sustainable talent management strategy that focuses on individual employee needs to improve organizational loyalty and performance.